Transcriptional regulation of the three grapevine chalcone synthase genes and their role in flavonoid synthesis in Shiraz. (30th May 2013) - Harris, N.N.; Luczo, J.M.; Robinson, S.P.; Walker, A.R.
Abstract Background and Aims Chalcone synthase (CHS) catalyses the first committed step of the flavonoid pathway that leads to the synthesis of anthocyanins, tannins and flavonols. In the grapevine, CHS is encoded by three similar genes (VvCHS1, 2, 3). Their expression patterns and regulation by MYB transcription factors were determined to identify the role of these three genes in the biosynthesis of different flavonoid compounds. Methods and Results Quantitative polymerase chain reaction analysis indicated that the transcript level of VvCHS1 and VvCHS2 correlated with both flavonol and tannin accumulation in Shiraz vegetative and berry tissues, and in cell cultures. The transcript level of all three VvCHS genes correlated with an increase of anthocyanins in berry skins indicating their role in anthocyanin synthesis. MYB transcription factors regulating tannin and flavonol synthesis activated the VvCHS1 and VvCHS2 promoters, while all of the grapevine flavonoid MYB genes tested activated the VvCHS3 promoter to different degrees. Analysis of the VvCHS promoter sequences indicated key differences in the identifiable binding motifs. Conclusions Distinct accumulation patterns of the three VvCHS transcripts in response to environmental and developmental cues are achieved through regulation by pathway‐specific MYB factors. Significance of the Study The three grapevine genes encoding CHS are temporally and spatially regulated by MYB transcription factors to produce different flavonoid compounds in a range of tissues, and these contribute to grape and wine composition.